2011
DOI: 10.3113/fai.2011.0344
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Multi-Center Feasibility Trial of rhPDGF-BB versus Autologous Bone Graft in a Foot and Ankle Fusion Model

Abstract: Based on the available data, the rate of radiographic union, time to full weightbearing, and outcomes scores between the Augment™ and ABG subjects appear comparable. Augment™ may represent a safe and efficacious treatment alternative to ABG during foot and ankle arthrodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 25 publications
0
57
0
5
Order By: Relevance
“…38 The research group did, however, show a 14% nonunion rate (2/14). 38 Based on blinded CT scan analysis, healing rates (defined as 50% osseous bridging) were mildly different: 69% (9/13) of the treatment group showed healing, whereas 60% (3/5) in the ICBG group healed. 38 They reported no significant adverse effects related to this orthobiological combination.…”
Section: Platelet-derived Growth Factormentioning
confidence: 87%
See 2 more Smart Citations
“…38 The research group did, however, show a 14% nonunion rate (2/14). 38 Based on blinded CT scan analysis, healing rates (defined as 50% osseous bridging) were mildly different: 69% (9/13) of the treatment group showed healing, whereas 60% (3/5) in the ICBG group healed. 38 They reported no significant adverse effects related to this orthobiological combination.…”
Section: Platelet-derived Growth Factormentioning
confidence: 87%
“…38 This group also found that the use of ICBG added 26 minutes to the surgery on average compared to the rhPDF/TCP combination. 38 A study by Daniels et al 39 also evaluated a product consisting of recombinant human PDGF with a calcium phosphate matrix (TCP). This was a prospective multicenter study with 60 patients and primarily designed to test this compound's safety in hindfoot or midfoot fusion.…”
Section: Platelet-derived Growth Factormentioning
confidence: 93%
See 1 more Smart Citation
“…Among the PDGF isoforms, PDGF-BB is considered ‘universal’, mainly due to its ability to bind to both known forms of PDGF-receptor isotypes. In the musculoskeletal system, recombinant human PDGF-BB injection therapy has already been employed in experimental and clinical studies to promote fracture healing and foot and ankle fusion rates (27,28). It is considered important in upregulating cytokines that enhance osseous and soft-tissue healing and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…A related rPDGF/β-TCP product, AUGMENT® (BioMimetic Therapeutics) has been evaluated as a healing adjunct in foot and ankle surgeries and distal radius fractures. A randomized, controlled pilot study suggested that AUGMENT® was at least as effective as autologous bone graft in stimulating hindfoot and ankle fusion [182]. …”
Section: Gfs Commonly Used For Bone Tissue Engineering Applicationsmentioning
confidence: 99%